Analisis “Lihat Sekitar” Buku Ajar untuk Kelas IV SD/MI Bab 4 (Meliuk dan Menerjang) Tahun 2023 Berbasis Kelayakan Buku BSNP - Nayla Rachma Putri Widyasari; Panca Dewi Purwati; Elya Anggita Dewi; Aulia Nawa Wulandari; Irma Ayu Diana; Alya Bunga Aura (FKIP, Universitas Palangka Raya, 2025)
Textbooks play an important role in the learning process because they are the main source for students and teachers in achieving the set learning outcomes (CP). However, the suitability of the contents of the textbooks needs to be reviewed to ensure their compliance with national education standards. This study aims to (1) analyze the suitability of the contents of Chapter 4 of the Indonesian Language textbook for grade IV SD/MI based on elements and learning outcomes; (2) evaluate the accuracy and novelty of the material; (3) examine the use of language in delivering the material; and (4) assess the presentation and graphical appearance of the book according to BSNP standards. This study uses a content analysis method with an assessment instrument based on the textbook suitability indicators according to the National Education Standards Agency (BSNP). The object of the study is the Indonesian Language textbook for grade IV SD/MI entitled